Basics of Education Focus on ECS Report - Charles E. Litz; Gerald D. Bailey (Educational Considerations, 1985)
What makes a good school good? How do students learn… These questions and their answers are the focus of Education Advisory: 1985, released this winter by the Education Commission of the States (ECS).